2020
DOI: 10.1186/s12967-020-02550-2
|View full text |Cite
|
Sign up to set email alerts
|

Classification models using circulating neutrophil transcripts can detect unruptured intracranial aneurysm

Abstract: Background Intracranial aneurysms (IAs) are dangerous because of their potential to rupture. We previously found significant RNA expression differences in circulating neutrophils between patients with and without unruptured IAs and trained machine learning models to predict presence of IA using 40 neutrophil transcriptomes. Here, we aim to develop a predictive model for unruptured IA using neutrophil transcriptomes from a larger population and more robust machine learning methods. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…We performed differential gene expression analysis between the samples of different TOAST classes in edgeR, as previously reported 11 12. In edgeR, we estimated common dispersion for all genes and performed differential expression testing on each transcript using an exact test analogous to Fisher’s exact test.…”
Section: Methodsmentioning
confidence: 99%
“…We performed differential gene expression analysis between the samples of different TOAST classes in edgeR, as previously reported 11 12. In edgeR, we estimated common dispersion for all genes and performed differential expression testing on each transcript using an exact test analogous to Fisher’s exact test.…”
Section: Methodsmentioning
confidence: 99%
“…Transcriptome profiling is a powerful tool for revealing expression patterns that are associated with complex diseases [9,15,16], such as stroke. The ability to extract satisfactory RNA from blood clots for downstream applications has been proven difficult with traditional extraction methods.…”
Section: Discussionmentioning
confidence: 99%
“…We performed a quantitative reverse transcription-polymerase chain reaction (RT-qPCR) as previously described [7][8][9]. Primers were created for three housekeeping genes: GAPDH, GPI, and HPRT1.…”
Section: Rt-qpcrmentioning
confidence: 99%
“…Circulating neutrophils were shown to carry a signature related to IAs, providing a possibility to diagnose patients with IAs based on biomarkers in peripheral blood (23). Based on the circulating neutrophil transcriptome data, Meng et al constructed a model to predict unruptured IAs (24); this model was further improved by the integration of machine learning approaches and large cohorts (25). Quan et al reported that the expression of F2-isoprostanes and F4-neuroprostanes in the plasma of patients with IAs is significantly upregulated compared with healthy subjects, and these may be considered potential biomarkers for IA development (26).…”
Section: Discussionmentioning
confidence: 99%